Religion and contemporary management: Moses as a model for effective leadership - Wolak, Arthur J. ca. 20./21. Jh. (Anthem Press, 2016)
Ancient leadership for present times -- Defining leadership -- Leaders and managers -- Heroism, charisma, and their limitations -- Empathic leadership -- Humility, the antithesis of arrogance -- Moses' essential leadership skills -- Assessing Moses' leadership style